2015
DOI: 10.1021/np500909b
|View full text |Cite
|
Sign up to set email alerts
|

Myxochelins Target Human 5-Lipoxygenase

Abstract: Extracts of the predatory myxobacterium Pyxidicoccus fallax HKI 727 showed antiproliferative effects on leukemic K-562 cells. Bioactivity-guided fractionation led to the isolation of the bis-catechol myxochelin A and two new congeners. The biosynthetic origin of myxochelins C and D was confirmed by feeding studies with isotopically labeled precursors. Pharmacological testing revealed human 5-lipoxygenase (5-LO) as a molecular target of the myxochelins. In particular, myxochelin A efficiently inhibited 5-LO act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…We recently described the isolation of the catechol siderophore myxochelin A from the predatory bacterium Pyxidicoccus fallax HKI727 . The natural product strongly suppressed the growth of K‐562 leukemia cells and pharmacological characterization revealed human 5‐LO as the molecular target, which was inhibited with an IC 50 of 1.9 μ m in a cell‐free assay . The active site of human 5‐LO contains a non‐heme iron, which serves as an electron donor (Fe 2+ ) or acceptor (Fe 3+ ) during catalysis .…”
Section: Structures Of Lysinol‐derived Myxochelin Analogues and Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently described the isolation of the catechol siderophore myxochelin A from the predatory bacterium Pyxidicoccus fallax HKI727 . The natural product strongly suppressed the growth of K‐562 leukemia cells and pharmacological characterization revealed human 5‐LO as the molecular target, which was inhibited with an IC 50 of 1.9 μ m in a cell‐free assay . The active site of human 5‐LO contains a non‐heme iron, which serves as an electron donor (Fe 2+ ) or acceptor (Fe 3+ ) during catalysis .…”
Section: Structures Of Lysinol‐derived Myxochelin Analogues and Theirmentioning
confidence: 99%
“…[7] The naturalp roduct strongly suppressedt he growth of K-562 leukemiac ells and pharmacological character-ization revealed human 5-LO as the molecular target, which was inhibited with an IC 50 of 1.9 mm in ac ell-free assay. [7] The active site of human 5-LO contains an on-heme iron, which serves as an electron donor (Fe 2 + )o ra cceptor( Fe 3 + )d uring catalysis. [8][9][10] Our original assumption that the inhibition of human5 -LO was solely due to the complexation of this active site iron by myxochelinA could be disproven by structure activity relationship (SAR) studies of myxochelind erivatives which were generated by precursor-directedb iosynthesis.…”
mentioning
confidence: 98%
“…Pseudochelin A is a catechol siderophore that is structurally closely related to the myxochelins (10,13) and hyalachelins (14). In this study, we identified a gene cluster for pseudochelin A biosynthesis in P. piscicida S2040 and we demonstrated that a single enzyme, MxcM, is needed to provide a myxochelin-producing bacterium the potential for pseudochelin biosynthesis.…”
Section: Discussionmentioning
confidence: 81%
“…In recent years, myxobacteria have gained increasing attention due to their enormous potential as producers of secondary metabolites with antifungal, antibacterial, and cytotoxic activities (7)(8)(9). To maintain their iron homeostasis, many myxobacteria produce catechol siderophores, such as the myxochelins (10)(11)(12)(13) or the structurally related hyalachelins (14). Although the myxochelins are generally regarded as myxobacterial siderophores, they were occasionally also described for other bacteria.…”
mentioning
confidence: 99%
“…Pyxidicoccus sp. in this study produces compounds that are inhibitory to pancreatic (MIA PaCa-2) and prostate (PC-3) cancer cell lines, whereas a secondary metabolite from P. fallax has been associated with inhibition of leukemic cells by Schieferdecker et al (2015). In the present investigation, the extract from M. fulvus (S199) exhibited the inhibition of PC-3 (prostate cancer) and HeLa (cervical cancer) cells which have not been documented in the cytotoxicity profile of the metabolite isolated from M. fulvus in a study by Ahn et al (1999).…”
Section: Discussionmentioning
confidence: 91%